(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To investigate the acute and sub-chronic toxicity of standardized extracts from Lai Chau ginseng cultivated in Sin Ho District, Lai Chau Province. Subjects and methods: The standardized extract of Lai Chau ginseng was prepared at the Traditional Medicine Hospital of Ho Chi Minh City from 5-year-old Lai Chau ginseng (Panax vietnamensis var. fuscidiscus K.Komatsu, S.Zhu & S.Q.Cai) grown at an altitude above 2,000 meters in Sin Ho district, Lai Chau province. Acute and sub-chronic toxicity studies were conducted on Swiss albino mice. Results: The Lai Chau ginseng extract showed no acute toxicity, with a maximum tolerated dose (Dmax) of 49.39 g/kg. The extract did not affect general physical condition or induce changes in hematological, biochemical parameters, or histological structure of the heart, liver, and kidneys in the mice administered doses of 75, 150, and 300 mg/kg over a period of 60 days. Conclusion: Lai Chau ginseng extract was found to be non-toxic in mice.